2012
DOI: 10.1037/a0026885
|View full text |Cite
|
Sign up to set email alerts
|

Social appraisal influences recognition of emotions.

Abstract: The notion of social appraisal emphasizes the importance of a social dimension in appraisal theories of emotion by proposing that the way an individual appraises an event is influenced by the way other individuals appraise and feel about the same event. This study directly tested this proposal by asking participants to recognize dynamic facial expressions of emotion (fear, happiness, or anger in Experiment 1; fear, happiness, anger, or neutral in Experiment 2) in a target face presented at the center of a scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 53 publications
4
86
1
2
Order By: Relevance
“…In line with such findings, some authors have found that individuals decide how to react and respond to social situations according to their perceptions of others' facial expressions and past experiences with them [16,17].…”
Section: Emotional Appraisal Process and Affect Statesmentioning
confidence: 70%
“…In line with such findings, some authors have found that individuals decide how to react and respond to social situations according to their perceptions of others' facial expressions and past experiences with them [16,17].…”
Section: Emotional Appraisal Process and Affect Statesmentioning
confidence: 70%
“…Additionally, one's perception of emotionally relevant stimuli (e.g., faces) is also influenced by a social partner's facial expression and gaze direction. Mumenthaler and Sander (2012) demonstrated that participants' recognition of a target fear face was facilitated by the presence of a second face looking toward the target face while expressing anger. A key element for discriminating or uniting the terms social referencing and social appraisal lies in the outcome for the individual, specifically whether one's own emotional experience, be it operationalized as appraisal or behavior, is affected by the emotional communication of the social other.…”
Section: Defining Social Referencingmentioning
confidence: 99%
“…Similarly, Hornik et al (1987) describe "the infant form [ing] an appraisal of novel events based on the mother's affective reaction" (p. 943). Furthermore, studies of both terms indicate that the communication of the social partner may be ostensive (e.g., Parkinson et al, 2012;Sorce et al, 1985), but that this is not criterial (e.g., Boccia & Campos, 1989;de Rosnay, Cooper, Tsigaras, & Murray, 2006;Mumenthaler & Sander, 2012). Rather, the processes are characterized by the motivation of the individual seeking emotional information, not the motivation of the individual being referenced.…”
Section: Defining Social Referencingmentioning
confidence: 99%
See 2 more Smart Citations